Comparative study of five serological assays for the diagnosis of paraneoplastic pemphigus. Issue 1 (January 2015) - Kelly, Shane; Culican, Suzanne; Silvestrini, Roger A.; Vu, Jacinta; Schifter, Mark; Fulcher, David A.; Lin, Ming-Wei
Abstract : Summary: Paraneoplastic pemphigus (PNP) is an autoimmune mucocutaneous blistering disease driven by autoantibodies against plakins expressed in mucosal epithelium. Diagnosis can be difficult as both clinical and biopsy features overlap with other blistering disorders, thus serology is important. Indirect immunofluorescence (IIF) on rat bladder substrate is the most widely used assay, but plakin-specific autoantibody assays have recently become available. The aim of this study was to compare the performance of five PNP assays in patients with mucosal blistering disease: IIF with rat bladder, monkey bladder and rat cardiac substrates, an envoplakin enzyme-linked immunosorbent assay (ELISA), and an envoplakin-transfected HEK cell based assay (CBA). Fifty-one patient serum samples, comprising three PNP patients and 48 disease controls, were collected along with 10 healthy control samples, and analysed using the five assays. IIF on rat and monkey bladder substrates both showed high specificity (97% and 95%, respectively), and correctly identified all three PNP sera. The envoplakin ELISA was equally specific (98%) but identified only one PNP patient. The CBA was difficult to interpret, and both this assay and IIF on rat cardiac substrate lacked specificity (82% and 83%, respectively). In this study IIF using either rat or monkey bladder substrates performed strongly, whilst the envoplakin ELISA seemed to lack sensitivity, and the CBA and IIF on rat cardiac substrate were inferior. Our findings suggest that traditional IIF-based assays remain the preferred approach in the serological diagnosis of PNP.